Utilization of marine gypsum as an alternative to mineral gypsum in the reclamation of degraded sodic soil and as a means of enhancing crop productivity. (12th July 2022) - Jha, Sunil Kumar; Mishra, Vinay Kumar; Damodaran, Thukkaram; Singh, Yash Pal; Sharma, Parbodh Chander
Abstract: For sustainable management of degraded sodic soils, mineral gypsum (GYP) has been widely used, but supplies are limited, industrialization, and urbanization have thwarted its use in agriculture. Therefore, there is a need to develop alternative ameliorants to GYP. We conducted a field experiment on degraded sodic soil (pH‐10.2) using marine gypsum (MG), a waste/by‐product of the edible salt (NaCl) manufacturing process. Based on gypsum requirement (GR) of soil, efficacies of GYP and MG, at equivalent doses, were compared for reclamation of sodic soil using treatments: control, 50 GR GYP, 50 GR MG, 25 GR GYP, 25 GR MG, and 25 GR GYP + 25 GR MG. The results showed a significant decrease in soil pH following appliation of 50 GR MG compared with other treatments. The reduction in exchangeable sodium percentage was found and to be highest (50.78%) in 50 GR MG among all treatments but statistically identical to 50 GR GYP. The net dispersive charge we noted was a minimum of 4.04 cmol kg −1 for 50 GR MG but was on par with 50GR GYP and 25GR GYP + 25GR MG. The presence of MgCl2, NaCl, and KCl as impurities in marine gypsum assisted its dissolution by increasing the ionic strength of solution and facilitated Ca 2+ release for exchange reactions. We found the average yield of rice and wheat to be statistically similar for applications of 50 GR MG, 50 GR GYP, and 25 GR GYP + 25 GR MG. Thus, our study suggests that MG could effectively be used as an alternative ameliorant for the reclamation of degraded sodic soil without compromising crop yields, under scarce availability of GYP.